2000
DOI: 10.1080/00207230008711307
|View full text |Cite
|
Sign up to set email alerts
|

A study of nitrate in Tehran ground water and a method of its removal

Abstract: This study investigates the concentration of nitrate in groundwater in the province of Tehran. It also proposes the combination of ion exchange and biological denitrification as an effective way of removing nitrate from drinking water. The concentration of nitrate was measured in more than 200 deep and semi-deep wells spread throughout urban and rural areas in Tehran. The result proved the presence of nitrate in a wide area in the province, especially in the southern part of the city of Tehran, and areas next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Furthermore, NO 3 − >100 mg/L was observed in two sampling locations in the TPW in dry period, which is far greater than the permissible level in drinking water. Previous studies also reported high concentration of NO 3 − in Tehran's water resources, especially for the groundwater resources that mainly located in the southern regions of this city (Imandel et al, 2000;Torabian et al, 2000;Joekar-Niasar and Ataie-Ashtiani, 2009;Ghahremanzadeh et al, 2018;Noori et al, 2019;Nejatijahromi et al, 2019). However, contamination of water resources by NO 3 − is a global concern, especially in highly populated area with dense agricultural lands.…”
Section: 𝐍𝐎 𝟑 − and 𝐍𝐎 𝟐 − Concentration In Tehran's Potable Watermentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, NO 3 − >100 mg/L was observed in two sampling locations in the TPW in dry period, which is far greater than the permissible level in drinking water. Previous studies also reported high concentration of NO 3 − in Tehran's water resources, especially for the groundwater resources that mainly located in the southern regions of this city (Imandel et al, 2000;Torabian et al, 2000;Joekar-Niasar and Ataie-Ashtiani, 2009;Ghahremanzadeh et al, 2018;Noori et al, 2019;Nejatijahromi et al, 2019). However, contamination of water resources by NO 3 − is a global concern, especially in highly populated area with dense agricultural lands.…”
Section: 𝐍𝐎 𝟑 − and 𝐍𝐎 𝟐 − Concentration In Tehran's Potable Watermentioning
confidence: 71%
“…Previous studies examined the quality of water resources with a direct focus on waterworks (i.e. wells, rivers, and dam reservoirs), that partially supply drinking water for Tehran metropolis (Imandel et al, 2000;Torabian et al, 2000;Joekar-Niasar and Ataie-Ashtiani, 2009;Mohseni-Bandpei et al, 2018;Nejatijahromi et al, 2019). Although taking samples from the waterworks can provide useful information to determine the degree of exposure for end-users (Schullehner et al, 2017), they are not entirely representative of supplied water, given that the TPW comes from a mixture of both surface-and ground-waters.…”
Section: Samplingmentioning
confidence: 99%
“…The chemical properties of the water of the Qanat are shown in Table 1. To achieve the desired influent nitrate concentration (150 mg/L), KNO 3 was added to the influent (32). The inoculum was obtained from the returned anoxic activated sludge of the A2O process treating municipal wastewater in the Shahrak-e-Ekbatan wastewater treatment plant in Tehran (Iran).…”
Section: Methodsmentioning
confidence: 99%
“…The challenges related to the clean-groundwater supply associated with nitrate are more severe in the densely populated regions located in developing countries such as Iran, particularly in the Tehran–Karaj aquifer 39 – 43 . Tehran–Karaj plain has struggled with issues like rapid urbanization, rising population, increased agricultural and industrial activities, and unbalanced use of fertilizers, which led to elevated nitrate in groundwater 44 .…”
Section: Introductionmentioning
confidence: 99%